2007
DOI: 10.1080/03031853.2007.9523769
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural cooperatives II: Can they facilitate access of small-scale farmers in South Africa to input and product markets?

Abstract: The objective of this research is to investigate whether agricultural cooperatives can facilitate smallholder farmer access to input and product markets. Farmers in two case study communal areas of KwaZulu-Natal face high transaction costs as reflected primarily in their low levels of education and literacy, lack of market information, insecure property rights, poor road and communication infrastructure, and long distances to markets. Analysis of the reasons why cooperatives were originally established in vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(80 citation statements)
references
References 8 publications
4
75
0
1
Order By: Relevance
“…Farmer group membership helps in accessing information important in production, post-harvest practices and marketing (Garikai, 2014). Ortmann and King (2007) stated the reasons for the formation of farming cooperatives and farmer group organisations including promotion of self-help, improving negotiating strength with input suppliers and buyers of farm products, assurance of input supplies and/or product markets mainly for perishable crops like fruits and vegetables, and reduction of opportunistic behaviour brokers. The lack of participation in these farmer groups meant lack of access to information on production, post-harvest handling of French bean and marketing and this may have negative effect on the overall yield achieved by the farmers.…”
Section: Discussionmentioning
confidence: 99%
“…Farmer group membership helps in accessing information important in production, post-harvest practices and marketing (Garikai, 2014). Ortmann and King (2007) stated the reasons for the formation of farming cooperatives and farmer group organisations including promotion of self-help, improving negotiating strength with input suppliers and buyers of farm products, assurance of input supplies and/or product markets mainly for perishable crops like fruits and vegetables, and reduction of opportunistic behaviour brokers. The lack of participation in these farmer groups meant lack of access to information on production, post-harvest handling of French bean and marketing and this may have negative effect on the overall yield achieved by the farmers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that social capital, in its different forms, played a crucial role to adopt different adaptation options to reduce environmental shocks that came out from climate variability and change [32,81,82]. For instance, Mpogole [82] found that increased membership to social groups would increase the probability of adopting conservation agriculture, drought-tolerant varieties, and irrigation.…”
Section: Social Capitalmentioning
confidence: 99%
“…Cooperatives require highly committed, skilled and well-experienced leaders. Dedicated and competent leaders in SPCs are cornerstones to access information about product markets, and to maintain the quality of seed production (Ortmann and King 2007). Strong leaders are able to increase members' commitment (Fulton and Giannakas 2001).…”
Section: Challenges For Seed Producer Cooperativesmentioning
confidence: 99%